Anticholinergic discontinuation and cognitive functions in patients with schizophrenia: a pharmacist–physician collaboration in the outpatient department - Sathienluckana T; Unaharassamee W; Suthisisang C; Suanchang O; Suansanae T (Dove Medical Press, 2018)
Thanompong Sathienluckana,1 Weerapon Unaharassamee,2 Chuthamanee Suthisisang,3 Orabhorn Suanchang,4 Thanarat Suansanae5 1Faculty of Pharmacy, Siam University, Bangkok, Thailand; 2Department of Psychiatry, Somdet Chaopraya Institute of Psychiatry, Bangkok, Thailand; 3Department of Pharmacology, Faculty of Pharmacy, Mahidol University, Bangkok, Thailand; 4Department of Pharmacy, Somdet Chaophraya Institute of Psychiatry, Bangkok, Thailand; 5Department of Pharmacy, Faculty of Pharmacy, Mahidol University, Bangkok, Thailand Introduction: Cognitive impairment is a core feature and shows the highest impact on functional outcome in patients with schizophrenia. There have been no previous studies investigating the role of the pharmacist in a multidisciplinary team on cognitive outcomes in patients with schizophrenia. Purpose: We evaluated the impact of pharmacist intervention on cognitive outcomes in patients with schizophrenia by focusing on anticholinergic discontinuation. Patients and methods: A prospective, open-label, randomized, controlled study was conducted. Patients with schizophrenia were randomly assigned to either the pharmacist intervention or usual care groups. In the pharmacist intervention group, the pharmacist identified drug-related problems (DRPs) and provided a pharmacotherapy suggestion, while there was no intervention in the usual care group. The primary outcome was mean change from baseline of executive function by using Wisconsin Card Sorting Test (WCST) perseverative errors within the pharmacist intervention group at week 12. Results: A total of 30 patients completed the study (13 in the pharmacist intervention group and 17 in the usual care group). WCST perseverative errors at the end of the study within the pharmacist intervention group improved significantly from baseline (P=0.003). DRPs at week 12 were reduced by 85.19% and 9.76% in the pharmacist intervention and usual care groups, respectively. The most common intervention was the discontinuation of anticholinergics in patients without extrapyramidal side effects. Conclusion: Added-on pharmacist intervention in a multidisciplinary team could help to improve cognitive functions in patients with schizophrenia by reducing DRPs and optimizing the drug therapy regimen, especially for anticholinergic discontinuation. Keywords: pharmacist intervention, cognitive functions, schizophrenia, anticholinergic